Multi-pass layup process for thermoplastic composites using robotic fiber placement. (February 2018) - Zhao, Pan; Shirinzadeh, Bijan; Shi, Yaoyao; Cheuk, Simeon; Clark, Leon
Highlights: The dominant factor in compaction force that affects the underneath layers is presented. The model of compaction force affected the length of different layers is established. The optimization method for improving the uniformity of bonding strength of each interlaminar interface is proposed. Effectiveness of the optimization method is verified by experiments. Abstract: Robotic fiber placement is a promising technique to manufacture complex components for industry. Compaction pressure, hot gas torch temperature and laying velocity are the key molding factors for fiber placement process, and their optimal selection directly affects the product performance. Small compaction pressure, low gas temperature and fast laying velocity lead to incomplete interlaminar adhesion and high porosity. However, excessive compaction pressure, high gas temperature and slow laying velocity lead to excessive resin extrusion from the contact surface of the two layers, thus affecting the overall structural rigidity of the laminates. At the same time, due to the forming characteristics of fiber placement process, the compaction pressure has an impact on each underneath layer under the influence of heat transfer and laying velocity, which results in different interlaminar bonding strength between the different layers. This study aims at analyzing and optimizing the robotic fiber placement process parameters to obtain the composite laminate with the homogeneity of interlaminar bonding strength. Based on analyzing the heat transfer from current contact surface to each one underneath, the multi-pass compaction pressure from non-deformable roller affecting the underneath layers is investigated, and experiments are conducted to verify the optimizing method.